Teledermatology in low resource settings: the MSF experience with a multilingual tele-expertise platform - Sophie eDelaigue; Jean-Jacques eMorand; David eOlson; Richard eWootton; Richard eWootton; Laurent eBONNARDOT; Laurent eBONNARDOT (Frontiers Media S.A., 2014)
INTRODUCTIONIn 2010, Médecins Sans Frontières (MSF) launched a tele-expertise system to improve the access to specialized clinical support for its field health workers. Among medical specialties, dermatology is the second most commonly-requested type of tele-expertise. The aim of the present study was to review all MSF teledermatology cases in the first four years of operation. Our hypothesis was that the review would enable the identification of key areas for improvement in the current MSF teledermatology system.METHODSWe carried out a retrospective analysis of all dermatology cases referred by MSF field doctors through the MSF platform from April 2010 until February 2014. We conducted a quantitative and qualitative analysis based on a survey sent to all referrers and specialists involved in these cases.RESULTSA total of 65 clinical cases were recorded by the system and 26 experts were involved in case management. The median delay in providing the first specialist response was 10.2 hours (IQR 3.7-21.1). The median delay in allocating a new case was 0.96 h (IQR 0.26, 3.05). The three main countries of case origin were South Sudan (29%), Ethiopia (12%) and Democratic Republic of Congo (10%). The most common topics treated were infectious diseases (46%), inflammatory diseases (25%) and genetic diseases (14%). One-third of users completed the survey. The two main issues raised by specialists and/or referrers were the lack of feedback about patient follow up and the insufficient quality of clinical details and information supplied by referrers.DISCUSSIONThe system clearly delivered a useful service to referrers because the workload rose steadily during the 4-year study period. Nonetheless, user surveys and retrospective analysis suggest that the MSF teledermatology system can be improved by providing guidance on best practice, using pre-filled referral forms, following-up the cases after teleconsultation and establishing standards for clinical photography.